Rethinking the Improvement of the Compilation Content and Planning System of Territorial Spatial Planning - Hao Qing (Redai dili, 2021)
Territorial spatial planning is the optimization and adjustment of territories for modern countries in response to environmental changes in development. Since 2018, China has gradually established a territorial spatial planning system and has carried out the compilation of territorial spatial planning. In recent years, significant changes have taken place in the development environment—both domestically and abroad—illustrating the trends of shortened-chains and the regionalization of the global economy, intelligent and digital production and manufacturing, low-carbon and green social development, aging populations, and the presence of minority populations, all of which have a systematic and profound impact on China's economic and social development, as well as territory development and protection. Territorial spatial planning must be a response to the prevailing context timely. On one hand, China has a vast territory, a large population, obvious regional differences, and a huge market space. Therefore, it is necessary to build a new pattern of territory development and protection to coordinate both economic and social development and territory development, promote the matching between humans and nature, and improve the quality of economic development and people's quality of life. Territorial spatial planning should (1) support the "dual circulation" pattern with the domestic cycle as the main body and improve the efficiency of the national economy; (2) strengthen the comprehensive competitiveness and innovation capabilities of urban agglomerations and metropolitan areas to increase the carrying capacity of populations and industries; (3) build a new type of infrastructure that adapts to the new development concept; (4) and reconstruct the spatial patterns to respond to demographic changes. On the other hand, it is necessary to further improve the territorial spatial planning system, enhance the strategy of overall spatial planning, give full play to the professionalism of special planning, improve the humanistic nature of detailed planning, formulate and implement cross-regional spatial planning, improve the institutional mechanism of continuous spatial governance, and comprehensively improve the capacity of spatial governance and the modernization level of the governance system.